Peripheral blood natural killer cell percentages in granulomatosis with polyangiitis correlate with disease inactivity and stage - Merkt, Wolfgang; Lasitschka, Felix; Tretter, Theresa; Saure, Daniel; Hundemer, Michael; Schwenger, Vedat; Blank, Norbert; Lorenz, Hanns-Martin (Arthritis Research & Therapy, 2015)
The role of CD3−CD56+ natural killer (NK) cells in granulomatosis with polyangiitis (GPA) is poorly understood. Recently, it has been shown that peripheral blood NK cells can kill renal microvascular endothelial cells, suggesting a pathogenic role of NK cells in this disease. So far, subset distribution, phenotype, and function of peripheral blood NK cells in relation to GPA disease activity have not been elucidated. Moreover, it is not known whether NK cells infiltrate GPA tissue lesions.
Gesehen am 29.05.2020